The Influence ff The Debate Learning Method on Population and Environmental Material on Learning Outcomes and Scientific Habits of Mind of Class IX Students at SMP Negeri 1 Ngabang - Ike Viki Dwi Astuti; Hanum Mukti Rahayu; Mahwar Qurbaniah (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
This study aims to determine the effect of the debate learning method on population and environmental materials on learning outcomes and Scientific habits of mind of class IX students at SMP Negeri 1 Ngabang. This study used the Quasy Experimental method. Tihis research design used Nonequivalent Control Group Design with simple random sampling method with the number of 25 students. The data collection technique uses a learning achievement test and a scientific habits of mind questionnaire. Learning outcomes with an average pretest score in the control class is 36 and the experimental class is 41.6. The average posttest scores in the control and experimental classes were 64.4 and 82.8. The average gain in experimental class learning outcomes is 41.2 while the average gain in control class learning outcomes is 28.4. The effect of the debate method on learning outcomes is 51.6% with an Effect Size value of 0.9 while the debate method on Scientific habits of mind is 81.1% with an Effect Size value of 2.0. So it can be concluded that debate learning has a great influence on student learning outcomes and scientific habits of mind.